2018
DOI: 10.1113/jp275094
|View full text |Cite
|
Sign up to set email alerts
|

NMDA receptor‐gated visual responses in hippocampal CA1 neurons

Abstract: Hippocampal processing of environmental information is critical for hippocampus-dependent brain functions that result from experience-induced hippocampal plasticity, such as memory acquisition and storage. Hippocampal responses to sensory stimulation have been extensively investigated, particularly with respect to spike activity. However, the synaptic mechanism for hippocampal processing of sensory stimulation has been much less understood. Here, we performed in vivo whole-cell recording on hippocampal CA1 pyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 33 publications
0
9
1
Order By: Relevance
“…Non-spatial information has been reported to largely ow into the ventral and anterior hippocampus 18 .Visual signals project to the hippocampus from the visual cortex through a multi-synaptic pathway 19,20 . Previous studies found that hippocampal activity could represent visual stimuli 4 , and neurons in the hippocampus and visual cortex showed synchrony in visual stimuli experiments 21 . The transmission pathways between the hippocampus and auditory cortex are complex.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Non-spatial information has been reported to largely ow into the ventral and anterior hippocampus 18 .Visual signals project to the hippocampus from the visual cortex through a multi-synaptic pathway 19,20 . Previous studies found that hippocampal activity could represent visual stimuli 4 , and neurons in the hippocampus and visual cortex showed synchrony in visual stimuli experiments 21 . The transmission pathways between the hippocampus and auditory cortex are complex.…”
Section: Discussionmentioning
confidence: 92%
“…It has been demonstrated to support a "spatial cognitive map", providing an environment-centric spatial memory system 1,2 . Apart from encoding spatial information, previous studies have revealed that the hippocampal neuronal network also encodes non-spatial information such as visual 3,4 , auditory 5,6,7 , olfactory 8,9 , gustatory 10 , and tactile 11,12 . These observations indicate a more abstract and comprehensive hippocampal cognitive map, formally generating a high-dimensional space for both spatial and nonspatial information.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated to support a “cognitive map”, providing an environment-centric spatial memory system (O’keefe and Nadel, 1978; Spiers et al, 2020). Apart from encoding spatial information, previous studies have revealed that the hippocampal neuronal network also encodes non-spatial information such as visual (Acharya et al, 2016; Liu et al, 2018), auditory (Moita et al, 2003; Itskov et al, 2012; Xiao et al, 2018), odour (Komorowski et al, 2009; Taxidis et al,2020), gustatory (Ho et al, 2011), and tactile information (Pereira et al, 2007; Gener et al, 2013). These intriguing observations indicate a more abstract and comprehensive hippocampal cognitive map, generating a high-dimensional space for both spatial and non-spatial information.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated to support a "cognitive map", providing an environment-centric spatial memory system Spiers et al, 2020). Apart from encoding spatial information, previous studies have revealed that the hippocampal neuronal network also encodes non-spatial information such as visual (Acharya et al, 2016;Liu et al, 2018), auditory Itskov et al, 2012;Xiao et al, 2018), odour Taxidis et al,2020), gustatory (Ho et al, 2011), and tactile information (Pereira et al, 2007;Gener et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the presence of NMDA receptor-mediated responses in hippocampal CA1 neurons, a synaptic mechanism for hippocampal processing that may play important roles in hippocampus-dependent functions such as learning and memory [ 17 ].…”
Section: Introductionmentioning
confidence: 99%